Valuing damages for green accounting purposes: The GARP II approach - Anil Markandya; Alistair Hunt; Pamela Mason (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper reports the results of a four country project (GARPII) on aspects of green accounting, namely the estimation of damages to air and water. The countries covered are Germany, Italy, Netherlands and the United Kingdom. It follows an earlier project covering the same countries, which was a first attempt to provide national level damage estimates on a spatially disaggregated basis for key air pollutants (GARPI). GARPII covers more pollutants and also attributes the damages to sources - industry, power generation transport etc. This paper reports the key results of the project and compares the methodology used with that of an alternative methodology - the GREENSTAMP approach.
Keywords: Q2; Q3; O47; 330; Environmental national accounting; dosage assessment; Umweltökonomische Gesamtrechnung; Umweltbelastung; EU-Staaten